2022
DOI: 10.1002/jctb.7240
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the bioconversion of ferulic acid from alkaline hydrolysate of corn cobs to vanillin by Amycolatopsis thermoflava under nutrient limitation and reducing sugar control

Abstract: BACKGROUND The use of commercially available ferulic acid (FA) as a precursor for vanillin production is costly. The utilization of agro‐waste as a starting material provides an alternative to obtain FA at a low cost and establish an economically profitable production system. In this work, optimization of ultrasound‐assisted extraction conditions for releasing FA from corn cobs using alkaline treatment was conducted. Further, bioconversion of FA from the crude hydrolysate of corn cobs to vanillin using Amycola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
3
2
Order By: Relevance
“…However, the yield of ferulic acid and vanillin was very low that is, 0.46 mg vanillin/g ferulic acid. In another study, alkaline hydrolysate of corn cob was used to produce 0.28 g/L of vanillin per g/L of ferulic acid 25 . This vanillin titer is slightly higher than the titer in the current study; however, the extracted ferulic acid yield is much lower.…”
Section: Resultscontrasting
confidence: 55%
See 4 more Smart Citations
“…However, the yield of ferulic acid and vanillin was very low that is, 0.46 mg vanillin/g ferulic acid. In another study, alkaline hydrolysate of corn cob was used to produce 0.28 g/L of vanillin per g/L of ferulic acid 25 . This vanillin titer is slightly higher than the titer in the current study; however, the extracted ferulic acid yield is much lower.…”
Section: Resultscontrasting
confidence: 55%
“…In another study, alkaline hydrolysate of corn cob was used to produce 0.28 g/L of vanillin per g/L of ferulic acid. 25 This vanillin titer is slightly higher than the titer in the current study; however, the extracted ferulic acid yield is much lower. Torres et al 21 have also reported vanillin production from the alkaline hydrolysate of corn cob using genetically engineered Escherichia coli JM109/pBB1.…”
Section: Biotransformation Of An Isolated Ferulic Acid Stream By Adap...contrasting
confidence: 65%
See 3 more Smart Citations